KONSUMSI LITERASI DIGITAL: SOLUSI QUR’ANI UNTUK MENJAGA KREDIBILITAS KEILMUAN - Faradila, Nadia; Husna, Maisarotil; Islamiyah (LPPM STAI Muhammadiyah Probolinggo, 2025)
The development of digital technology has drastically changed information consumption, including in Islamic science. This phenomenon presents a significant challenge to scientific credibility because religious information is often spread without a clear sanad, even through artificial intelligence (AI) that has no ethical awareness, triggering a crisis of da'wah authority. This research aims to analyze the Qur'an's view of digital literacy, identify the challenges of digital religious information consumption, and formulate Qur'anic strategies to maintain the credibility of Islamic science. The method used is library research with a qualitative-descriptive approach and content analysis, focusing on Qur'anic verses and relevant literature. The results show that the consumption of digital literacy, especially by the younger generation, leads to a shift in scientific epistemology from sanad authority to algorithm-based content. The Qur'an emphasizes the importance of tabayyun (QS. Al-Hujurat: 6), wisdom in preaching (QS. An-Nahl: 125), as well as the use of common sense (ululalbab) (QS. Az-Zumar: 9) and the ability to read and write (QS. Al-'Alaq: 1-5) as the foundation of literacy. In conclusion, Qur'anic solutions to maintain scientific credibility in the digital era include four main strategies: strengthening digital literacy education, applying adab and ethics in the dissemination of knowledge, strict information filtering and verification, as well as collaboration between scholars and technology, such as the development of the